TINJAUAN EKONOMI SYARIAH TERHADAP PENINGKATAN EKONOMI KELURGA DALAM AKTIVITAS PENJUALAN PAKAN TERNAK DI DESA ARJASA KECAMATAN ARJASA KABUPATEN SITUBONDO - Hali Makki; Arif Hariyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Notional noetic in this case, purpose of this study is to determine the practice or activity of buying and selling animal feed in Arjasa Situbondo Village, this study uses a qualitative descriiptive approach, combining primary file or interview resulta sharia economic review of the activity of buying and selling animal feed in accordance with the viesw of fiqh scholars, both in terms of buying and selling contracts and the prevalling pillars of buying and selling.